PEMENUHAN HAK KREDITOR SEPARATIS SEBAGAI PEMEGANG HAK JAMINAN DALAM KEPAILITAN - Muhammad Danu Syachputra (2022)
There are two legal subjects in Indonesia, namely individuals and legal entities. In carrying out a business activity, the legal subject requires business capital. The party who gives the loan is known as the creditor while the party who receives the loan is called the debtor. The position of creditors is regulated in the Civil Code starting from Article 1132. In the settlement of bankruptcy assets, it is regulated in Law no. 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations (Bankruptcy Law and PKPU). There are Separatist, Preferred and Concurrent Creditors. This study uses empirical juridical research methods, namely legal research methods that use primary data and secondary data such as provisions, norms, regulations, and legal rules. The results of this study are that if the separatist creditor wants to execute the object of the guarantee, there are still several obstacles, for example the refusal from third parties such as workers because their wages have not been fulfilled, then the controlling third party does not want to vacate the object of collateral, the object that is the object of the guarantee has been transferred to third parties. So that separatist creditors do not get legal certainty.